Understanding the properties of tailor-made self-assembled monolayers with embedded dipole moments for interface engineering - Gärtner, Michael; Sauter, Eric; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2018)
Self-assembled monolayers (SAMs) are frequently used for interfacial dipole engineering in organic electronics and photovoltaics. This is mostly done by the attachment of dipolar tail groups onto the molecular backbone of the SAM precursors. The alternative concept of embedded dipoles involves the incorporation of polar group(s) into the backbone. This allows one to decouple the tuning of the electrostatic properties of the SAM from the chemical identity of the SAM-ambient interface. Here we present design and synthesis of particularly promising SAM precursors utilizing this concept. These precursors feature the thiol-docking group and a short heteroaromatic backbone, consisting of a nonpolar phenyl ring and a polar pyrimidine group, embedded in two opposite orientations. Packing density, molecular orientation, structure, and wetting properties of the SAMs on Au substrates are found to be nearly independent of their chemical structure, as shown by a variety of complementary experimental techniques. A further important property of the studied SAMs is their good electrical conductivity, enabling their application as electrode modifiers for low-contact resistances in organic electronic devices. Of particular interest are also the electronic properties of the SAMs, which were monitored by Kelvin probe and high-resolution X-ray photoelectron spectroscopy measurements. To obtain a fundamental understanding of these properties at an atomistic level, the experiments were combined with state-of-the-art band structure calculations. These not only confirm the structural properties of the films but also explain how the C 1s core-level binding energies of the various atoms are controlled by their chemical environments in conjunction with the local distribution of the electrostatic potential within the monolayer.